2015
DOI: 10.1016/j.apmr.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional Independence After Inpatient Rehabilitation for Traumatic Brain Injury Among Minority Children and Adolescents

Abstract: Objective To compare motor and cognitive functional independence scores between Hispanic, non-Hispanic Black (NHB) and non-Hispanic White (NHW) children with traumatic brain injury (TBI) after discharge from inpatient rehabilitation. Design Retrospective cohort study using the Uniform Data System for Medical Rehabilitation national dataset from years 2002–2012. Setting Inpatient rehabilitation units. Participants 10,141 children 6 months to 18 years of age who received inpatient rehabilitation for TBI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…As with the previous study of children with TBI, 8 this study found racial/ethnic and insurance-based differences in receipt of rehabilitation at children’s hospital–based rehabilitation units. This study’s findings of improved efficiency of rehabilitation admissions with shorter lengths of stay at children’s hospital–based rehabilitation units suggest that children, particularly those with impairments affecting cognitive function, would be best served at rehabilitation units within a children’s hospital setting.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As with the previous study of children with TBI, 8 this study found racial/ethnic and insurance-based differences in receipt of rehabilitation at children’s hospital–based rehabilitation units. This study’s findings of improved efficiency of rehabilitation admissions with shorter lengths of stay at children’s hospital–based rehabilitation units suggest that children, particularly those with impairments affecting cognitive function, would be best served at rehabilitation units within a children’s hospital setting.…”
Section: Discussionsupporting
confidence: 82%
“…8 The development of evidence-based and expert-endorsed quality-of-care indicators focusing on the structure, organization, and processes of care of pediatric inpatient rehabilitation was undertaken with the ultimate goal of improving patients’ outcomes. The quality-of-care indicators focused on those that may affect functional outcomes for children with TBI 15 but will likely operate similarly for children with all diagnoses relevant to inpatient pediatric rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to this study, a recent study found the effect of Hispanic and Non-Hispanic Black race/ethnicity on discharge function after inpatient rehabilitation for TBI was non-significant after adjustment for other variables including insurance status [26]. …”
Section: Discussionsupporting
confidence: 79%